Investigation using whole genome sequencing of a prolonged restaurant outbreak of Salmonella typhimurium linked to the building drainage system, England, February 2015 to March 2016 - Mair-Jenkins, John; Borges-Stewart, Roberta; Harbour, Caroline; Cox-Rogers, Judith; Dallman, Tim; Ashton, Philip; Johnston, Robert; Modha, Deborah; Monk, Philip; Puleston, Richard (European Centre for Disease Prevention and Control, 2017)
Following notification of a Salmonella enterica serovar Typhimurium gastroenteritis outbreak, we identified 82 cases linked to a restaurant with symptom onset from 12 February 2015 to 8 March 2016. Seventy-two cases had an isolate matching the nationally unique whole genome sequencing profile (single nucleotide polymorphism (SNP) address: 1.1.1.124.395.395). Interviews established exposure to the restaurant and subsequent case-control analysis identified an association with eating carvery buffet food (adjusted odds ratios (AOR): 20.9; 95% confidence interval (CI): 2.2 - infinity). Environmental inspections, food/water testing, and a food trace-back investigation were inconclusive. Repeated cycles of cleaning were undertaken, including hydrogen peroxide fogging, however, transmission continued. After 7 months of investigation, environmental swabbing identified 106 isolates from kitchen surfaces and restaurant drains matching the outbreak profile. We found structural faults with the drainage system and hypothesised that a reservoir of bacteria in drain biofilm and underfloor flooded areas may have sustained this outbreak. Ineffective drain water-traps (U-bends) may have also contributed by allowing transmission of contaminated aerosols into the kitchen environment. These findings suggest that routine swabbing of sink drain points and inspection of drainage systems should be considered in future outbreak scenarios.